Synthesis and characterization of electrospun molybdenum dioxide–carbon nanofibers as sulfur matrix additives for rechargeable lithium–sulfur battery applications - Zhuang, Ruiyuan; Yao, Shanshan; Jing, Maoxiang; Shen, Xiangqian; Xiang, Jun; Li, Tianbao; Xiao, Kesong; Qin, Shibiao (Beilstein Journal of Nanotechnology, 2018)
One-dimensional molybdenum dioxide–carbon nanofibers (MoO2–CNFs) were prepared using an electrospinning technique followed by calcination, using sol–gel precursors and polyacrylonitrile (PAN) as a processing aid. The resulting samples were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, Brunauer–Emmet–Teller (BET) surface area measurements, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). MoO2–CNFs with an average diameter of 425–575 nm obtained after heat treatment were used as a matrix to prepare sulfur/MoO2–CNF cathodes for lithium–sulfur (Li–S) batteries. The polysulfide adsorption and electrochemical performance tests demonstrated that MoO2–CNFs did not only act as polysulfide reservoirs to alleviate the shuttle effect, but also improve the electrochemical reaction kinetics during the charge–discharge processes. The effect of MoO2–CNF heat treatment on the cycle performance of sulfur/MoO2–CNFs electrodes was examined, and the data showed that MoO2–CNFs calcined at 850 °C delivered optimal performance with an initial capacity of 1095 mAh g−1 and 860 mAh g−1 after 50 cycles. The results demonstrated that sulfur/MoO2–CNF composites display a remarkably high lithium–ion diffusion coefficient, low interfacial resistance and much better electrochemical performance than pristine sulfur cathodes.
Keywords: electrochemical performance; electrospinning; lithium–sulfur batteries; MoO2–CNFs; sulfur matrix